2021
DOI: 10.3892/mmr.2021.12495
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 knockdown suppresses inflammation, apoptosis and extracellular matrix degradation in IL-1β-induced chondrocytes by activating PPARγ to regulate the NF-κB signaling pathway

Abstract: Osteoarthritis (OA) is a common degenerative disease that can lead to severe joint pain and loss of function, seriously threatening the health and normal life of patients. At present, the pathogenesis of OA remains to be clarified. Recent studies have shown that fatty acid-binding protein 4 (FABP4) is increased in the plasma and synovial fluid of patients with OA. However, the effect of FABP4 on OA is unclear. The present study established IL-1β-induced ATDC5 cells with FABP4 knockdown. Next, cell viability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Interestingly, the upregulation of FABP4 was also observed in the articular cartilage of RA mice. Since a previous study showed that IL-1β could stimulate the expression of FABP4 in ATDC5 cells (a chondrogenic cell line), 50 we hypothesized that FABP4 upregulation in RA chondrocytes was induced by excessive proinflammatory factors (IL-1β, IL-6 and TNF-α) derived from synovial M1 macrophages, FLSs and ECs. These data demonstrated that FABP4 secretion by synovial macrophages exacerbated cartilage degeneration by disrupting chondrocyte homeostasis through activation of the NF-κB pathway in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the upregulation of FABP4 was also observed in the articular cartilage of RA mice. Since a previous study showed that IL-1β could stimulate the expression of FABP4 in ATDC5 cells (a chondrogenic cell line), 50 we hypothesized that FABP4 upregulation in RA chondrocytes was induced by excessive proinflammatory factors (IL-1β, IL-6 and TNF-α) derived from synovial M1 macrophages, FLSs and ECs. These data demonstrated that FABP4 secretion by synovial macrophages exacerbated cartilage degeneration by disrupting chondrocyte homeostasis through activation of the NF-κB pathway in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FABP4 produced in epicardial/perivascular fat and macrophages within the atherosclerotic lesion upregulates inflammation-related pathways, leading to the development of coronary atherosclerosis [ 14 ]. FABP4 also increases inflammatory cytokines and mediates apoptosis in a variety of cell types [ 15 , 27 ]. The regulation of inflammation and apoptosis seems to be strongly related since FABP4 silencing protects from cardiomyocyte or chondrocyte apoptosis via the master regulator of the inflammation nuclear factor-κB (NF-κB) pathway [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 also increases inflammatory cytokines and mediates apoptosis in a variety of cell types [ 15 , 27 ]. The regulation of inflammation and apoptosis seems to be strongly related since FABP4 silencing protects from cardiomyocyte or chondrocyte apoptosis via the master regulator of the inflammation nuclear factor-κB (NF-κB) pathway [ 15 , 27 ]. Conversely, the downregulation of FABP4 using its specific inhibitor BMS309403 can suppress inflammation and/or apoptosis in pathological settings including acute lung injury, acute kidney injury, or diabetic nephropathy [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is regarded as a transcriptional factor that is activated by several pro-inflammatory cytokines. It is closely related to inflammation, apoptosis, oxidative stress, and the extracellular matrix degradation of chondrocytes [ 39 ]. The ubiquitin–proteasome pathway is a major proteolytic pathway.…”
Section: Discussionmentioning
confidence: 99%